Determination of Tourism Sector Service Management through Consumer Satisfaction: Analysis of Service Quality and Consumer Trust - Yuliantini Yuliantini; Olfebri Olfebri; Aang Gunawan; Lira Agusinta (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to analyze the influence of service quality and consumer trust on service management in Indonesia's tourism sector, with consumer satisfaction serving as a mediating variable. The study employs a descriptive qualitative approach using the Literature Review method. Data were collected reputable scientific articles indexed in national databases (SINTA) and international databases, including Scopus, Web of Science, Emerald, and Elsevier. The analysis process consisted of data reduction, data presentation, and conclusion drawing to develop a comprehensive conceptual framework. The findings reveal that service quality has a significant influence on consumer satisfaction and service management. Consumer trust also positively affects consumer satisfaction and service management. Furthermore, consumer satisfaction plays a crucial role in enhancing tourism service management. The study confirms that consumer satisfaction mediates the relationship between service quality and service management, as well as between consumer trust and service management. These results indicate that both technical aspects of service delivery and relational factors such as trust are essential determinants of effective tourism service management. This study contributes to the development of an integrative tourism service management model by combining service quality, consumer trust, and consumer satisfaction into a unified framework. The proposed model provides both theoretical insights and practical implications for improving service performance and competitiveness in the tourism industry.